The Hamilton affair : a novel - Cobbs, Elizabeth (Arcade Publishing, 2016)
Set against the dramatic backdrop of the American Revolution, and featuring a cast of iconic characters such as George Washington, Thomas Jefferson, and the Marquis de Lafayette, The Hamilton Affair tells the sweeping, tumultuous, true love story of Alexander Hamilton and Elizabeth Schuyler, from tremulous beginning to bittersweet ending his at a dueling ground on the shores of the Hudson River, hers more than half a century later after a brave, successful life.